Improved Irritative Voiding Symptoms 3 Years after Stereotactic Body Radiation Therapy for Prostate Cancer - Rana, Zaker; Cyr, Robyn A.; Chen, Leonard N.; Kim, Brian S.; Moures, Rudy A.; Yung, Thomas M.; Lei, Siyuan; Collins, Brian T.; Suy, Simeng; Dritschilo, Anatoly; Lynch, John H.; Collins, Sean P. (Frontiers in Oncology, 2014)
Background: Irritative voiding symptoms are common in elderly men and following prostate radiotherapy. There is limited clinical data on the impact of hypofractionated treatment on irritative voiding symptoms. This study sought to evaluate urgency, frequency, and nocturia following stereotactic body radiation therapy (SBRT) for prostate cancer. Methods: Patients treated with SBRT monotherapy for localized prostate cancer from August 2007 to July 2011 at Georgetown University Hospital were included in this study. Treatment was delivered using the CyberKnife® with doses of 35–36.25 Gy in five fractions. Patient-reported urinary symptoms were assessed using the International Prostate Symptom Score (IPSS) before treatment and at 1, 3, 6, 9, and 12 months post-treatment and every 6 months thereafter. Results: Two hundred four patients at a median age of 69 years received SBRT with a median follow-up of 4.8 years. Prior to treatment, 50.0% of patients reported moderate to severe lower urinary tract symptoms (LUTS) and 17.7% felt that urinary frequency was a moderate to big problem. The mean prostate volume was 39 cc and 8% had prior procedures for benign prostatic hyperplasia. A mean baseline IPSS-irritative (IPSS-I) score of 4.8 significantly increased to 6.5 at 1 month (p < 0.0001), however returned to baseline at 3 months (p = 0.73). The IPSS-I score returned to baseline in 91% of patients by 6 months and 96% of patients by 2 years. Transient increases in irritative voiding symptoms were common at 1 year. The mean baseline IPSS-I score decreased to 4.4 at 24 months (p = 0.03) and 3.7 at 36 months (p < 0.0001). In men with moderate to severe LUTS (IPSS ≥ 8) at baseline, the mean IPSS-I decreased from a baseline score of 6.8–4.9 at 3 years post-SBRT. This decrease was both statistically (p < 0.0001) and clinically significant (minimally important difference = 1.45). Only 14.6% of patients felt that urinary frequency was a moderate to big problem at 3 years post-SBRT (p = 0.23). Conclusion: Treatment of prostate cancer with SBRT resulted in an acute increase in irritative urinary symptoms that peaked within the first month post-treatment. Irritative voiding symptoms returned to baseline in the majority of patients by 3 months post-SBRT and were actually improved from baseline at 3 years post-SBRT.